Endobronchial metastasis of testicular germ cell tumor - Turan, Demet; Ozgul, Mehmet Akif; Kirkil, Gamze; Cetinkaya, Erdogan (Kare Publ, 2018)
Endobronchial metastasis (EBM) of extrapulmonary malignancies is rarely reported; on the other hand, germ cell tumors (GCTs) are extremely rare. This report describes a case of a testicular germ cell tumor presenting as a polypoid endobronchial mass. A 48-year-old male patient had a history of hemoptysis for several weeks. He had undergone orchiectomy due to testicular GCT 20 years ago. Computerized tomography of the thorax obtained endobronchial polypoid lesion in the right intermediate bronchus. Rigid bronchoscopy was applied; right intermediate bronchus was obliterated with a polypoid lesion. The lesion was coagulated with argon plasma coagulation, and debris was removed by biopsy forceps. Pathological examination of the specimen was somatic-type GCT. No recurrence was observed during the follow-up of the patient. We want to present our case to emphasize the importance of distinguishing EBM from primary lung carcinoma which treatment and survival are quite different.
Keywords: Endobronchial metastasis; germ cell tumors; intrabronchial therapy